3-IN-1 HYBRID LEARNING ENVIRONMENT. Issue 2 (3rd April 2021) - Hapke, Holly; Lee-Post, Anita; Dean, Tereza
ABSTRACT: We propose a learning innovation called 3-in-1 Hybrid environment as a solution for educational institutions to meet the challenge of balancing campus reopening against public health risks amid the COVID-19 pandemic. Our proposed innovation provides students options to attend class synchronously (either face-to-face or remote) or asynchronously (online) in an interactive learning environment that promotes emotional, behavioral, and cognitive engagement. We designed and implemented a large Marketing Management class with over 800 students as a 3-in-1 course. We examined its effectiveness in an empirical study and found that (1) students have a positive attitude toward 3-in-1 Hybrid learning; (2) they show a high level of synchronous attendance and a low number of missed quizzes and homework; and (3) their quiz performance is a strong mediator on the relationship between synchronous attendance and actual learning. Our study provides empirical evidence to support the promises of the proposed 3-in-1 Hybrid environment to address logistical and pedagogical challenges of student engagement in large class learning.